Determination of Social-Emotional Disorders Regarding The Use of Gadgets in Children Aged 5-6 Years Old at Lenterahati Islamic Boarding School Kindergarten, Indonesia - MA Muazar Habibi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study aims to determine the forms of gadget use and their social-emotional disorders in the children at Lenterahati Islamic Boarding School Kindergarten, West Sakra District, West Nusa Tenggara, Indonesia. The subjects involved in this descriptive qualitative analysis were 2 Kindergarten children aged 5-6 yrs old. The methods of data collection also involved interviews with children's parents, sample observation, and documentation. The results showed that both FH and AL subjects used gadgets almost on all occasions, with smartphones mostly utilized by the Kindergarten children in West Nusa Tenggara. Furthermore, the alternative used in the absence of phones was television. Based on these results, the impacts of these gadgets on children showed that their social-emotional developments were still very undeveloped. These undeveloped attributes included condition unadaptability, behavioural irresponsibility, tolerance, and appropriate emotion control. This indicated that both subjects often forgot to perform other activities and did not want to be disturbed when using these gadgets. Even when instructed by their parents to perform specific activities, they commonly displayed angry expressions. In addition, FH and AL were undisciplined, difficult to work with, and environmentally careless.